PENGEMBANGAN KURIKULUM DAN RENCANA PEMBELAJARAN SEMESTER (RPS) BERBASIS KKNI DI PERGURUAN TINGGI - Syafruddin Nurdin (al-fikrah: Jurnal Manajemen Pendidikan, 2018)
Development of KKNI-based curriculum in universities through two levels, namely macro and micro. At the macro level its development follows the stages, as follows: 1). Formulate the graduate profile, 2) Define the learning outcomes (Learning Outcomes), 3) Select the study materials, and 4) .Set the Course. While at the micro level (for implementation in class), development through Semester Learning Plan (RPS) which contains several components, as follows: a) .Identitas RPS, b). Learning Achievements, c). Indicators, d). Method of Learning, e). Time, f). Learning experience, g). Criteria and weighting scores, and h). Reference list.